Strategy as action : competitive dynamics and competitive advantage - Grimm, Curtis M. (Strategic management series (Oxford University Press), 2006)
Strategy as Action presents an action plan for how firms can build, improve, and defend their competitive advantage at every stage of their life cycle. For start-up firms entering a market, it provides a model for exploiting competitive uncertainty and blind spots; for growth firms who have established some market advantages, it provides an action plan for exploiting relative resources; for mature firms, it explains how to exploit market position; finally, for firms that have no decisive resource advantage, it provides an action plan based on firm co-operative reactions.